Target-Sequencing of Female Infertility Pathogenic Gene Panel and a Novel TUBB8 Loss-of-Function Mutation - Yuan, Hongxia; Chen, Jianhua; Li, Na; Miao, Hui; Chen, Yao; Lyu, Shuyan; Qiao, Yu; Yang, Guangping; Luo, Hui; Chen, Liangliang; Mao, Fei; Huang, Lingli; et al. (Frontiers in Genetics, 2022)
Genetic screening is an important approach for etiology determination and helps to optimize administration protocols in Reproductive Centers. After the first pathogenic gene of female infertility was reported in 2016, more and more new pathogenic genes were discovered and we sought to develop an efficient and cost-effective method for genetic screening in patients. In this study, we designed a target-sequencing panel with twenty-two female infertility-related genes including TUBB8, PATL2, WEE2 and PANX1, etc. and sequenced 68 primary infertility (PI) and recurrent pregnancy loss (RPL) patients. We sequenced 68 samples reaching an average depth of 1559× and detected 3134 variants. Among them, 62.2% are synonymous single-nucleotide variants (SNVs), and 36.3% are non-synonymous SNVs. The remaining 1.5% are indels (insertions and deletions) and stop-gains. DNAH11 and TUBB8 are the two genes that mutated most frequently. We also found a novel TUBB8 variant (c.898_900del; p.300_300del), proved its loss-of-function mechanism and profiled the interactome of wild-type (WT) and mutant TUBB8 proteins. Overall, this target-sequencing method provides an efficient and cost-effective approach for screening in IVF clinics and will support researchers for the discovery of new pathogenic variants.